Political Practice and Its Implication on Folk Art Marginalization (Case Study of Wayang Orang/ Human Puppet Ngesti Pandhowo) - Lanjari, Restu (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
The government, political practice, both reflected in the government, politics, policies and the attitude of the public figure, influences the existence of folk art that is overshadowed by changes as the results of modernization and industrialization. The aim of this research is to find out the marginalization of folk art because of political practice. This research was done using a qualitative approach while the subject of this research was Ngesti Pandhawa Human Puppet Group. The result of this research showed that folk art could be marginalized because of the influence of the changes in economic and politic that was formulated inside the modernization waves and technology development that offered new values. The attention of the government on the existence of folk art was still being questioned because of politic budget. The budget for art was extremely small compared to the budget for sport. The existence of folk art depended on the favor and interest of the local leaders, especially political interest.